Shallow Hal - Farrelly, Bobby, 1958-; Moynihan, Sean.; Farrelly, Peter; Paltrow, Gwyneth, 1972-; Black, Jack, 1969-; Alexander, Jason, 1959-; Viterelli, Joe, 1937-2004; Kirby, Rene.; McGill, Bruce, 1950-; Robbins, Anthony; Carpenter, Russell; Greenbury, Christopher; et al. ([United States] : 20th Century Fox Home Entertainment, 2002)
Following the advice of his dying father, Hal dates only physically beautiful women. One day, he runs into a self- help guru who hypnotises him into recognizing only the inner beauty of women. Hal then meets Rosemary, a grossly obese woman who Hal sees as a vision of loveliness. Will their relationship survive when Hal's equally shallow friend undoes the hypnosis and Hal sees the real Rosemary?
Originally produced as a motion picture in 2001.
Cinematography, Russell Carpenter ; editor, Christopher Greenbury.
Gwyneth Paltrow, Jack Black, Jason Alexander, Joe Viterelli, Rene Kirby, Bruce McGill, Anthony Robbins.
MPAA rating: PG-13.
DVD.
Closed-captioned.
Keywords: Superficiality -- Drama; Man-woman relationships -- Drama; Video recordings; Feature films; Comedy films